2021
DOI: 10.21775/cimb.040.081
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy: The Pharmacology of Antibacterial Viruses

Abstract: Pharmacology can be differentiated into two key aspects, pharmacodynamics and pharmacokinetics. Pharmacodynamics describes a drug's impact on the body while pharmacokinetics describes the body's impact on a drug. Another way of understanding these terms is that pharmacodynamics is a description of both the positive and negative consequences of drugs attaining certain concentrations in the body while pharmacokinetics is concerned with our ability to reach and then sustain those concentrations. Unlike the drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 272 publications
(333 reference statements)
0
41
0
1
Order By: Relevance
“…Cultures taken at 8 months were negative for the targeted bacteria, though the authors note that (p. 2018) "it is too early to know whether the infection has resolved completely." Though numbers of phages supplied in this case were fairly low for intravenous delivery [22], the infections targeted were localized. Therefore, it is certainly possible that phage replication in association with infecting bacteria could have made up for this delivered phage-titer deficit [119].…”
Section: Nir-paz Et Al 2019 a Baumannii And K Pneumoniae Osteomyelitismentioning
confidence: 87%
See 1 more Smart Citation
“…Cultures taken at 8 months were negative for the targeted bacteria, though the authors note that (p. 2018) "it is too early to know whether the infection has resolved completely." Though numbers of phages supplied in this case were fairly low for intravenous delivery [22], the infections targeted were localized. Therefore, it is certainly possible that phage replication in association with infecting bacteria could have made up for this delivered phage-titer deficit [119].…”
Section: Nir-paz Et Al 2019 a Baumannii And K Pneumoniae Osteomyelitismentioning
confidence: 87%
“…Phage treatments generally are thought to be more effective against newer, acute bacterial infections, e.g., when phage treatments are initiated days rather than months after the start of infections or indeed prophylactically [22], and this preference presumably stems from target bacteria not having yet entered into more phage-resistant physical or physiological states (e.g., [23]). In practice, however, published clinical treatments are typically of chronic or persistent bacterial infections [24], and particularly infections which antibiotic treatments have failed to cure [25][26][27][28].…”
Section: Complicating Factorsmentioning
confidence: 99%
“…It has also been shown that penetration to the bladder by Gram-negative phages, such as the T2 phage, is dose-dependent, and a minimum of 10 9 PFU/mL is needed for phage detection in the urine of mice after IV administration [89]. In addition, phage concentration in plasma was dependent on both dose and the route of administration, as explained previously [90,91].…”
Section: Pharmacokinetics Of Pseudomonas Phage Therapymentioning
confidence: 93%
“…The growth of two C. jejuni field strains, Cj18 or LH86, with and without exposure to four different Campylobacter bacteriophages vB_CjM-LmqsCP1-4 (CP1-4), vB_CjM-LmqsCP1-5 (CP1-5), vB_CjM-LmqsCP74-2c1 (CP74-2c1), and vB_CjM-LmqsCP132-3c (CP132-3c) at five different multiplicities of infection (MOI input of 10, 1, 0.1, 0.01, and 0.001) ( Danis-Wlodarczyk et al, 2021 ) was examined in liquid cultures using a Tecan Spark Microplate Reader with O 2 and CO 2 control, similar to methods described by Xie et al (2018) ; Rajnovic et al (2019) , and Zachary et al (2020) with some modifications. Briefly, phage suspensions were adjusted to 10 8 , 10 7 , 10 6 , 10 5 , and 10 4 PFU/ml, which were further diluted 10-fold with CBHI to achieve final dilutions of 10 7 , 10 6 , 10 5 , 10 4 , and 10 3 PFU/ml.…”
Section: Methodsmentioning
confidence: 99%